A decision-making framework for scheme selection for sustainable hydropower development. Issue 9 (15th July 2021) - Liu, Bingsheng; Yang, Ziyue; Chen, Yuan; Li, Ling; Chen, Si
ABSTRACT: Sustainable hydropower development has attracted widespread attention since the process of developing hydropower stations could negatively impact the social and ecological environments. However, the widely used decision-making approaches for selecting alternative schemes of hydropower stations focus primarily on cost-benefit analysis and do not fully consider a sustainability assessment framework. Therefore, this study proposes a decision-making framework that addresses scheme selection for hydropower development from a perspective of sustainability and hypothesizes that the optimal scheme determined by the proposed method will be consistent with the real decision result. First, an evaluation criteria system is established for assessing the sustainability features of alternative schemes, which includes social, environmental, and economic aspects. Considering the shortcomings of various methods that are used for multiple-criteria decision-making (MCDM), a new approach that is derived from multiple-attribute decision-making with time series is developed for hydropower development. Finally, considering a planned hydropower station of the Dadu River in China as an example, five alternative schemes are evaluated and analyzed by the proposed framework, and its effectiveness is illustrated through a comparison with an alternative method. The results demonstrate that the approach adopted in this study is effective for selecting the optimal scheme for developing a hydropower station sustainably, which can provide a reference for the establishment and evaluation of sustainability assessment systems for future hydropower development.